Pengaruh Pengungkapan Sustainability Report, Ukuran Perusahaan, dan Kesempatan Investasi terhadap Nilai Perusahaan - Clara Laurensia, Valerie; Purwaningrum, Supiningtyas; Niarti, Upi (Jurnal Ilmiah Raflesia Akuntansi, 2023)
Company value is a condition a company achieves based on investors' perception of the managers' success in managing company resources. Company value is often associated with stock prices, as the company's stock price is a market response to the overall condition of the company. This study aims to determine the influence of sustainability report disclosure, firm size, and investment opportunity set on company value. The research population consisted of 72 companies, and after using the purposive sampling method, 6 companies met the criteria selected. The data used in this study were quantitative in the form of annual reports and sustainability reports of food and beverage sub-sector companies listed on the Indonesia Stock Exchange from 2017-2021. The analysis technique used in this study was multiple linear regression analysis, preceded by testing the classical assumptions, including tests for normality, multicollinearity, autocorrelation, and heteroscedasticity. The results of this study indicate that sustainability report disclosure, firm size, and investment opportunity set collectively influence company value. However, sustainability report disclosure does not significantly affect company value. Firm size has a significant effect on company value, and investment opportunity set also has a significant effect on company value.